Risk factors for postpartum urinary incontinence: The impact of early-onset and late-onset Gestational Diabetes Mellitus in a nested case-control study - Sartorão Filho, Carlos I. [UNESP]; Pinheiro, Fabiane A. [UNESP]; Takano, Luiz [UNESP]; Prudêncio, Caroline B. [UNESP]; Nunes, Sthefanie K. [UNESP]; RLS, Hallur [UNESP]; Calderon, Iracema M.P. [UNESP]; Barbosa, Angélica M.P. [UNESP]; Rudge, Marilza V.C. [UNESP] (Elsevier, 2023)
Background: Gestational Diabetes Mellitus (GDM) and many other clinical variables have been associated with postpartum urinary incontinence (UI). However, the data are still restricted, and no study explored early- or late-onset GDM as a risk factor for this condition. We aimed to identify independent risk factors for postpartum UI, focusing on GDM and its early or late onset. Methods: A nested case control derived from the Diamater cohort study included 517 pregnant women who submitted to a planned C-section and followed by 6–18 months after delivery according to the timing of GDM diagnosis: early-onset GDM (before 20 weeks) and late-onset GDM(24–28 weeks) and the occurrence of UI. Results: Univariate analysis showed that the risk for 6–18 months postpartum UI was 49% higher in non-Caucasian ethnicity (1.49,1.02–2.18), 3,3 times higher in previous bariatric surgery [3.37,1.36–8.21], 39% higher in GDM women (1.39,1.01–1.93), and 5% higher for each BMI score in prepregnancy (1.05, 1.03–1.08) and at the end of pregnancy (1.05,1.02–1.08). Multivariate logistic regression analysis indicates that prepregnancy BMI was the only independent factor associated with the 6–18 months postpartum UI (adj 1.05, 95 %CI 1.02–1.08, P <.001). After stratifying, a second univariate and multivariate analysis were done according to the prepregnancy BMI cutoff score of 25. Thus, a significant association between GDM and postpartum UI in prepregnancy overweight women (RR: 1.91; 95 %CI 1.25–2.90, P =.003) and no association between GDM and 6–18 months postpartum UI in normal prepregnancy BMI (RR: 0.78, 95 %CI 0.39–1.54, P =.482) were found. After multivariate regression, the early-onset-GDM remained the unique independent adjusted risk factor for 6–18 months postpartum UI analysis (adjRR 2.15, 95 %CI 1.33–3.46, P =.002). Conclusion: After a planned C-section, we observed a 6–18 months postpartum UI higher occurrence after GDM, either in early-onset GDM or late-onset GDM. In addition, being overweight (BMI > 25) among women with early-onset GDM was associated with postpartum UI.
Keywords: Diabetes; Gestational; Hyperglycemia; Pregnancy; Urinary Incontinence